One-Minute Paper (OMP) as a Formative Assessment - Fritz Stephen Dadula Solamo (Indonesian Journal Of Educational Research and Review, 2022)
In the teaching process, several daily quiz points cannot guarantee an increase in the level of student understanding because it may be caused by different factors, one of which is the formative assessment applied to students who are not effective. The aims of this study is to analyse the effectiveness of a One-Minute Paper (OMP) as a formative assessment contribute meaningfully to increasing the scores of ninth grade of students on their summative assessment. This action research employed a quasi-experimental pre/post-test design. Subject of this study consist of fourteen students who were classified as experimental group who participated in the teacher-led discussion with the integration of one-minute paper as their formative assessment. The data obtain using open-ended question. Feedback-giving on the next day of class were done as part of the intervention. The result of study show a comparison group with fourteen students who were classified as control group had done the traditional way of formative assessment – the quiz. Both groups fall in the accepted region at 5% level of significance with mean gains of 9 and 6, respectively. It was revealed that the two methods were effective in increasing the scores of the students due to their higher mean scores. However, the experimental group’s mean gain score and mean percentage score (MPS) were significantly higher than the comparison group; thus, one-minute paper is more effective than quiz as a formative assessment.